Representations of animals on Greek and Roman engraved gems : meanings and interpretations - Sagiv, Idit, (Archaeopress Publishing Ltd, 2018)
A comprehensive study of the depictions of animals and their significance on Greek and Roman gems. The work examines the associations between animal depictions and the type of gemstone and its believed qualities. The study also compares the representation of animals on gems to larger media and analyses the differences.